RANCANG BANGUN ALARM BELL EMERGENCY STOP ESKALATOR BERBASIS MIKROKONTROLLER SEBAGAI MEDIA PEMBELAJARAN DI POLITEKNIK PENERBANGAN MAKASSAR - Ahmad Gaffar; Irfan; Andi Fadhilah Nugrah (Jurnal Penelitian, 2025)
Escalators are a crucial means of vertical transportation in various public facilities, such as airports. As a vocational educational institution, Makassar Aviation Polytechnic faces the challenge of providing adequate practical facilities, particularly for the 5th semester GSE Maintenance and Airport Equipment courses, which include escalators. This research project, a "Microcontroller-Based Escalator Emergency Stop Alarm Bell" system, has been successfully developed as an innovative learning tool at Makassar Aviation Polytechnic. This tool can simulate the escalator emergency stop mechanism, stop the motor, activate the alarm, and send emergency notifications. This learning tool is expected to enhance students' understanding of automatic control systems, IoT implementation, and escalator operational safety management, as well as provide an efficient solution for practical learning without the need for frequent field visits.